Lemierre's syndrome involving milleri group streptococci: further insight into age and aetiology. Issue 11 (23rd November 2020) - Linares, Christian A; Ryan, Felicity; Hajat, Imran; Glass, Stephen
Abstract : Lemierre's syndrome (LS) is a suppurative thrombophlebitis of the internal jugular vein secondary to otorhinolaryngologic infection. It is classically associated with the Gram-negative anaerobe Fusobacterium necrophorum (FN) and is thought to be a disease of young people. Here, we describe the case of a 56-year-old woman with LS involving milleri group streptococci (MGS), which has been reported only 13 times since it was first observed in 2003. Subgroup analysis of all published cases of LS involving MGS demonstrated these patients were significantly older than those involving FN (median age 49 years versus 18 years, p = 0.007, IQR 36–58 years), although this finding is limited by publication bias. This report clarifies a 2014 hypothesis regarding the relationship between age and aetiology in this rare disease. While FN remains the most common cause of LS overall, empiric antibiotic therapy should also cover oral streptococci such as MGS, even in younger adults.